« Un coup de dés jamais n’abolira le hasard » : quelques cas de conversions esthétiques au flamenco (XXe-XXIe siècles) - Vinciane Trancart (Cahiers de Civilisation Espagnole Contemporaine)
This work analyses the careers of flamenco artists who grew up outside Andalusia. Did they experience an aesthetic conversion or did an acculturation phenomenon occur? Based on interviews with the artists, this study takes into account the part of «biographical illusion» presented by P. Bourdieu: through souvenirs and discourse, these memories exposed are a result of the reconstruction of their experiences. We specifically analyse here the key founding moments of the discovery of flamenco, along with the decisions that brought these foreigners to devoting an essential part of their lives to an art that can be both distant from their culture of origin, but that has also become an integral part of their identity. Following a more or less quick and radical change, in what way did they decide or feel that they had become flamencos resulting from a crucial, even overwhelming discovery of new aesthetic references?